Does magnetically assisted capsule endoscopy improve small bowel capsule endoscopy completion rate? A randomised controlled trial - Hale, Melissa F.; Drew, Kaye; Sidhu, Reena; McAlindon, Mark E. (Endoscopy International Open, 2016)
Background and study aims: Delayed gastric emptying is a significant factor in incomplete small bowel capsule examinations. Gastric transit could be hastened by external magnetic control of the capsule. We studied the feasibility of this approach to improve capsule endoscopy completion rates. Patients and methods: Prospective, single-center, randomized controlled trial involving 122 patients attending for small bowel capsule endoscopy using MiroCam Navi. Patients were randomized to either the control group (mobilisation for 30 minutes after capsule ingestion, followed by intramuscular metoclopramide 10 mg if the capsule failed to enter the small bowel) or the intervention group (1000 mL of water prior to capsule ingestion, followed by positional change and magnetic steering). Outcome measures were capsule endoscopy completion rate, gastric clarity and distention, relationship of body habitus to capsule endoscopy completion rate (CECR), and patient comfort scores.Results: 122 patients were recruited (61 each to the control and intervention groups: mean age 49 years [range 21 – 85], 61 females). There was no significant difference in CECR between the two groups (P = 0.39). Time to first pyloric image was significantly shorter in the intervention group (P = 0.03) but there was no difference in gastric transit times (P = 0.12), suggesting that magnetic control hastens capsular transit to the gastric antrum but does not influence duodenal passage. Gastric clarity and distention were significantly better in the intervention group (P < 0.0001 and P < 0.0001 respectively). Conclusions: Magnetic steering of a small bowel capsule is unable to overcome pyloric contractions to enhance gastric emptying and improve capsule endoscope completion rate. Excellent mucosal visualisation within the gastric cavity suggests this technique could be harnessed for capsule examination of the stomach.